Sclerosing Rhabdomyosarcoma of the buccal mucosa: a cautionary tale - Omakobia, Eugene; Berridge, Natasha; Liew, Colin; Morley, Simon (Journal of Stomatology, 2015)
Rhabdomyosarcoma (RMS) is a malignant soft tissue tumour of skeletal muscle origin with a predilection for head and neck sites, including the oral cavity. Whilst RMS is the commonest soft tissue sarcoma in children, it is rare in adults, accounting for <1% of all malignancies. Three main histologic subtypes of RMS are recognised; namely embryonal, alveolar and pleiomorphic. There appears to be a newly emerging sclerosing variant which does not fit into the current classification. Here, we report an additional case of sclerosing RMS of the buccal mucosa in a 21 year old female. We place particular emphasis on the difficulties in diagnosis of RMS affecting the oral cavity; since many cases are initially misdiagnosed as infection of dental origin. This case not only serves as a useful reminder to clinicians not to forget this important diagnosis, but also contributes to the growing body of evidence supporting a new sclerosing variant of RMS.